Organic acid excretion from roots: a plant mechanism for enhancing phosphorus acquisition, enhancing aluminum tolerance, and recruiting beneficial rhizobacteria. Issue 6 (2nd November 2018) - Wu, Liujie; Kobayashi, Yuriko; Wasaki, Jun; Koyama, Hiroyuki
ABSTRACT: The beneficial effects of organic acids (OAs) excretion from plant roots were first proposed as being associated with the mechanism of superior phosphorus utilization by the cluster roots of white lupin ( Lupinus albus L.), and these effects are now widely accepted as pleiotropic effects associated with stress tolerance of plants. Excreted OAs detoxify rhizotoxic aluminum, recruit beneficial bacterium for induced systemic resistance, and modify root architecture to enhance phosphorus starvation. OA excretion is probably optimized in the carbon economy and is coordinately regulated with other traits that additively confer each stress factor. Here we present an overview of the molecular physiology of OA excretion from roots, how plants activate OA excretion, and how this excretion can be managed as a specific response.